Ion and neutral temperature distributions in the E-region observed by the EISCAT Tromsø and Svalbard radars - S. Maeda; S. Nozawa; M. Sugino; H. Fujiwara; M. Suzuki (Annales Geophysicae, 2002)
Simultaneous Common Program Two experiments by the EISCAT UHF radar at Tromsø and the EISCAT Svalbard radar at Longyearbyen from 00:00 to 15:00 UT on 22 September 1998 and 9 March 1999 have been utilized to investigate distributions of the ion and neutral temperatures in the E-region between 105 and 115 km. During the experiments, soft particle precipitations in the dayside cusp were observed over the Svalbard radar site by the Defense Meteorological Satellite Program (DMSP) F11 satellite. It is found that the dayside electric field in the regions of the low-latitude boundary of the polar cap and the cusp was greater and more variable than that in the auroral region. The ion temperature, parallel to the geomagnetic field at Longyearbyen, was higher than that at Tromsø during the daytime from 06:00 to 12:00 UT. The steady-state ion energy equation has been applied to derive neutral temperature under the assumption of no significant heat transport and viscous heating. The estimated neutral temperature at Longyearbyen was also higher than that at Tromsø. The ion and neutral energy budget was discussed in terms of the ion frictional heating and the Joule heating. The results indicate two possibilities: either the neutral temperature was high in the low latitude boundary of the polar cap and the cusp, or the heat transport by the polar cap neutral winds toward the dayside sector was significant. Key words. Ionosphere (auroral ionosphere; ionosphere–atmosphere interactions; polar ionosphere)